Readings in applied microeconomics : the power of the market - Newmark, Craig (London ; New York : Routledge, 2009)
This book supplements theoretical explanations of how markets work with concrete examples.
Information and incentives -- Creating value -- Property rights -- Externalities and coordination problems -- Non-excludable goods -- Asymmetric information -- Monopoly and collusion -- Abuse of firm power.
Includes bibliographical references and index.
aug 05/06/13; rpm 07/05/13
Loans
Keywords: Microeconomics